(untitled) (Research, Society and Development, 2021)
Currently, natural products are being used as a therapeutic alternative in the treatment and prevention of several diseases due to their low toxicity and relevant pharmacological potential. Thus, we can highlight basil (Ocimum basilicum L), one of the most used aromatic plants worldwide. Therefore, we provide some current evidence and insight into the potential therapeutic effect of basil essential oil to expand the available knowledge. A narrative review was carried out by searching electronic databases, providing a comprehensive analysis of the literature, where it was possible to identify existing problems and gaps to facilitate future research on basil essential oil. The available literature on basil essential oil presents us with several important pharmacological activities, such as: antioxidant, antiviral, antimicrobial, analgesic, anti-inflammatory, and analgesic and diuretic properties, among others. However, further research must be carried out to increase knowledge about this plant with enormous potential and determine its effectiveness and use in clinical conditions.